2015
DOI: 10.14236/jhi.v22i2.79
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm to improve diagnostic accuracy in diabetes in computerised problem orientated medical records (POMR) compared with an established algorithm developed in episode orientated records (EOMR)

Abstract: Background An algorithm that detects errors in diagnosis, classification or coding of diabetes in primary care computerised medial record (CMR) systems is currently available. However, this was developed on CMR systems that are episode orientated medical records (EOMR); and do not force the user to always code a problem or link data to an existing one. More strictly problem orientated medical record (POMR) systems mandate recording a problem and linking consultation data to them. Objective To compare the rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…This has to be adjusted for in analyses. 39 Finally, RCGP RSC data are probably the most up to date of the data sources, perhaps inevitably so, given the RSC's surveillance function. Data extracted up to the end of the previous week is analysed by noon on Wednesday and is in the public domain by 2 pm on Thursday of the following week.…”
Section: Comparison With Existing Literature and Other Uk Databasesmentioning
confidence: 99%
“…This has to be adjusted for in analyses. 39 Finally, RCGP RSC data are probably the most up to date of the data sources, perhaps inevitably so, given the RSC's surveillance function. Data extracted up to the end of the previous week is analysed by noon on Wednesday and is in the public domain by 2 pm on Thursday of the following week.…”
Section: Comparison With Existing Literature and Other Uk Databasesmentioning
confidence: 99%
“…EMIS, however, is an Episode Oriented Medical Record (EOMR) software, meaning that this linkage is not obligated. It is widely accepted that POMR-based systems reduce intra-patient coding variability, which assists in maintaining higher quality data 15. This study has demonstrated that data from CPRD and THIN account for the vast majority of research outputs from primary care databases.…”
Section: Discussionmentioning
confidence: 90%
“…The THIN database contains data exclusively from Vision/INPS, while QResearch uses only EMIS. Vision/INPS is a Problem Oriented Medical Record (POMR) software, meaning that it mandates the linkage of medical and drug information or visit consultations to a specific coded problem(s) 15. EMIS, however, is an Episode Oriented Medical Record (EOMR) software, meaning that this linkage is not obligated.…”
Section: Discussionmentioning
confidence: 99%
“…We call the latter episode orientated medical records (EOMR)! Using diabetes as an exemplar, we demonstrate how there are record-design-driven differences in coding practice and hence different strategies are needed for case finding 20. This work followed observations made in detailed multi-channel video observation of different computer systems 21,22.…”
Section: Clinical Informatics: Fatigue Child Maltreatment and More Amentioning
confidence: 89%